Analisa Devolusi Bphtb Menjadi Pajak Daerah Dengan Economic Of Collection Sebagai Tolak Ukur (Study Kasus Kabupaten Madiun) - Dewi Prastiwi; Amanta Zain; Yaman Suryaman (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2011)
AbstractAct No. 28 of 2009 is a set of policies issued by the government to give more autonomy to local government to manage its finances. One form of financial autonomy is realized in the form of devolution of authority from central government tax collections to the regional government, one of which is BPHTB. However, based on survey results of the readiness of the region with local regulation readiness indicators, from the 492 area there are only about 160 areas that are ready to pick BPHTB. The remaining 108 are in the process of preparing regional and 224 local law there is no information. Of the 224 areas that there is still no information is largely disagreed with the existence of such PDRD Act.Hence, this study aims to analyze the devolution of Economic BPHTB with the principle of Collection as a benchmark (especially in Madiun County). The results showed that in Madiun County policy did not represent one of the principle of taxation at the Economics of Collection. The results of this study can be used by governments as an ingredient to evaluate BPHTB devolution in general and review the levels of NJOPTKP determination as provided in Act No. 28 of 2009.